Evaluation of Elastomeric Impression in Fixed Partial Denture-A Retrospective Analysis of Patient Records - KARPAGAM, G. NITHYA; RAMANATHAN, VISALAKSHI; PRABU, DINESH (The journal of contemporary issues in business and government, 2021)
The aim of this study is to evaluate defects in the impressions made for fixed partial denture prosthesis. For this, patient records of those who underwent replacement of missing teeth with fixed partial denture were collected. A total of 50 fixed partial denture impressions were evaluated. The data collection was done considering the following parameters - impression technique, number of prepared units, defect in the facial margin , defect or cut through finish lines, defect onto the axial wall, defect in material polymerisation, exposure of heavy body through wash material, retraction cord embedded in impression, air bubbles and voids, type of tray used, number of cords preferred. The collected data was tabulated in excel sheet. Statistical analysis was done in SPSS software. This study shows that 90% were double wash impressions, 10% were single wash impressions. About 36% showed defects on the facial margin, 62% showed defective cuts through the 360 degree flash, 38% defect on the axial wall, 38% showed air bubbles and voids. Majority of the impressions were made after packing two cords. Within the limit of the present study it is concluded that double wash impression technique is the most preferred. The voids and bubbles were the majority of the defects that were present than any other defects.